Performance simulation of bio-reinforced composite car door panel using finite element analysis - Fatchurrohman, Nanang; Jun, Hew Xiao; Muhida, Rifki; Adelino, Muhammad Ilham (Institute of Electrical and Electronics Engineers Inc., 2021)
Interior car door panel serves as an interface between the interior of the car and the inner workings of the door, and between vehicle occupants and the door. They are expected to meet a variety of design specifications regarding safety, aesthetics, and functionality. The objective of this study is to compare the current acrylonitrile butadiene styrene (ABS) car door panel material with polylactic acid (PLA) reinforced kenaf fiber bio-reinforced composite material. The objective is to suggest a recommendation to car manufacturers on the performance of bio-reinforced composites as a new material for the car door panel. Finite Element Analysis (FEA) was conducted to simulate the performance and the results were obtained by determining stress and deformation. The results show that PL It shows that PLA-kenaf composite can absorb higher maximum von-Mises stress (214.13 MPa) if compared to ABS (211.26 MPa). The PLA-kenaf composites also show lower maximum total deformation (12.012 mm) if compared to ABS (42.501 mm). From the analysis, it can be concluded that PLA-kenaf composite has better performance than ABS, therefore has the potential to replace the current material used for car door panels.